Public responses and parasocial relationships following senator John Fetterman’s depression disclosure - Myrick, Jessica Gall; Willoughby, Jessica Fitts (Frontiers in Public Health, 2024)
Research has found that when public figures disclose an illness, it can motivate members of the public to reconsider their own related health-behaviors, particularly when the public experiences a parasocial relationship with that public figure. When the public figure is a politician, it is possible that partisan differences could also relate to emotional, attentional, and behavioral responses to health news. We empirically examined public responses to Democrat John Fetterman's disclosure of his treatment for depression shortly after being inducted into the United States Senate as the Junior Senator from Pennsylvania in 2023. Using a survey of adult Pennsylvania residents who identified as eligible voters in April of 2023, 204 respondents had heard the news of Fetterman's depression diagnosis and treatment.Our data reveal that differences in some demographics as well as parasocial relationships-positive and negative-with Fetterman predicted different patterns of emotional responses to the news. Additionally, age, anger, negative parasocial relationship, and a positive parasocial relationship were each associated with additional outcomes, including attention to news about the disclosure and depression-related information seeking. Mental health advocates could use politician's depression disclosures to provide information at a time when people are paying more attention to the condition; however, they may need to find other public figures to combat negative responses to partisan officials. Policy makers could also consider funding mental health campaigns that launch alongside public figure disclosures.